A Comparative Study of the Concept and Function of Separation of Powers in the Constitution of the Islamic Republic of Iran and Pakistan - Younes Fathi; Mohammad Mahdi Orvati Movaffagh (مطالعات تطبیقی حقوق کشورهای اسلامی, 2023)
Rulers in any country are more limited than the ruled as they are in charge of passing and enforcing laws as well as resolving disputes arising in the country. Distribution of power in the legislature, executive and judiciary and distinguishing the functions of each of these powers is a safeguard to preventing the concentration of power in the hands of a particular group or individual, which is called the Principle of Separation of Powers. Employing a descriptive-analytical approach, the present study investigates the separation of powers in the constitutions of the Islamic Republic of Iran and Pakistan. Commonalities and differences between the concept and function of separation of powers are compared and contrasted in the legal systems of the Islamic Republic of Iran and Pakistan. In the Constitution of the Islamic Republic of Iran, Article 57 recognizes the relative separation and independence of powers, as each power exercises its own powers under the supervision of the Supreme Leader. Although the constitution of the Islamic Republic of Pakistan does not mention the separation of powers, in various principles, the specific duties of each power are delineated and the function of separation of powers is perceivable. An account of the strengths and shortcomings of the two systems with deference to the principle of separation of powers could be helpful in ameliorating their functionality.